Tolylfluanid permeates human skin slowly and as dimethylamino sulfotoluidid (DMST). (15th May 2020) - Berthet, Aurélie; Hechon, Julie; Hopf, Nancy B.
Abstract: Tolylfluanid (TF) is a sensitizing biocide used in antifouling products and wood preservatives. Paint application is associated with skin exposure; however, the importance of this exposure route is uncertain as TF skin permeation rates are lacking in the peer-reviewed scientific literature. TF is a lipophilic powder that hydrolyses rapidly in contact with water to dimethylamino sulfotoluidid (DMST). DMST is also a TF metabolite. We characterized TF and DMST skin permeation using an ex vivo flow-through diffusion system with viable and frozen human skin. TF permeated as DMST with a low permeation rate (0.18 ± 0.05 μg/cm 2 /h) and a moderate time lag (7.1 ± 1.4 h) in viable human skin. Applying DMST gave a 3.5-fold lower permeation rate (0.05 ± 0.01 μg/cm 2 /h) compared to TF under a similar experimental setting. We simulated paint activities in an exposure chamber to understand a possible skin exposure from airborne TF concentrations. Although, paint can deposit onto the skin during work activities, TF permeation when paint was applied to human skin ex vivo was very low (as TF: 0.004 ± 0.005 μg/cm 2 /h, and as DMST: 0.02 ± 0.001 μg/cm 2 /h). Our results show that TF can permeate skin, and consequently, can contribute to sensitization, which support previous reports on sensitization in TF exposed workers.